Inflammatory cell infiltration in left atrial appendageal tissues of patients with atrial fibrillation and sinus rhythm - Hohmann, Christopher; Pfister, Roman; Mollenhauer, Martin; Adler, Christoph; Kozlowski, Jolanta; Wodarz, Andreas; Drebber, Uta; Wippermann, Jens; Michels, Guido (Scientific reports, 2020)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in clinical practice and is known to be associated with significant morbidity and mortality. Previous studies suggested a link between inflammation and AF by findings of increased inflammatory markers in AF patients. However, it has not been finally clarified whether inflammation is a systemic or a local phenomenon reflecting an active inflammatory process in the heart. To address this subject, human left atrial appendage tissues were obtained from 10 patients who underwent cardiac surgery and subjected to immunohistochemical analysis. The number of inflammatory CD3-positive T cells significantly increased from patients with sinus rhythm to paroxysmal AF and persistent AF, respectively. Interestingly, in patients with persistent AF, these cells were frequently arranged in small clusters. Subsequently, the number of inflammatory CD3-positive T cells decreased and was significantly lower in patients with permanent AF than in patients with persistent AF. Inflammatory CD20-positive B cells could only be detected very occasionally in all AF subgroups and were not locatable in patients with SR. Hence, our data emphasize the potential prominent role of the cellular component of the immune system in the development and perpetuation of AF.